Penggunaan Permainan Tebak Gaya Dalam Meningkatkan Kemampuan Berbicara Bahasa Arab: Pengaruh Permainan Tebak Gambar Untuk Meningkatkan Pemahaman Kosa Kata Bahasa Arab Di Surabaya - Nabielah Agustin Nabielah Agustin; Muhammad Rosyid Asy’ari (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2022)
The use of guessing games in improving the ability to speak Arabic. The game used as a medium for learning Arabic here is an educational game. Educational games are games that have educational elements that are obtained from something that exists and is attached and becomes part of the game itself. Vocabulary in Arabic or what is called mufradat, is a collection of words or a treasure trove of words that are known by a person or other ethnicity that is part of a particular language. Theoretical studies used are language games, games in language learning and Arabic learning media. This type of research is carried out using experiments. The aim is to determine the effect or causal relationship (causal relationship) by comparing the results of the experimental group given to the control group that was not given treatment. This study resulted in the pre-test results that the mastery of maharah kalam in Arabic lessons for students was in the medium category. This can be seen from the results of the pre-test, where less than 50 percent of students scored in the low category. And after the T-Test test on the results of the Pre Test and Post Test, it can be said that there is a significant difference in the results of learning Arabic using picture and mufrodat media in maharah kalam. Where the Mean Rank value in the pre test is 55.60 and the Mean Rank value in the post test is 82.80 for Surabaya students.